2015
DOI: 10.1177/0739986315578663
|View full text |Cite
|
Sign up to set email alerts
|

Latino Mothers’ and Fathers’ Caregiving With Their School-Age Children

Abstract: This study examined the levels of Latino mothers' and fathers' involvement in their school-age children's care and the relationships between parents' socio-economic status (SES) variables, sense of community, community provisions, and marital satisfaction with their involvement in children's routine and demand care. Mothers and fathers from 159 intact Latino families participated in the study. Multivariate analyses revealed that mothers spent significantly more time in providing child care than fathers did. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
7
2
Order By: Relevance
“…Thus, our finding is specific not only to parents' mothers but to female partners, as well. This finding is in contrast to the broader literature on the impact of partners on parenting outcomes, as most research seems to indicate that women's parenting tends to be more heavily influenced by their partners than does men's (Hossain et al, 2015;Yu et al, 2008). However, we find that Mexican-origin males appear more susceptible to partner influences as related to parenting satisfaction.…”
Section: The Moderating Roles Of Linguistic Acculturation and Parent contrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, our finding is specific not only to parents' mothers but to female partners, as well. This finding is in contrast to the broader literature on the impact of partners on parenting outcomes, as most research seems to indicate that women's parenting tends to be more heavily influenced by their partners than does men's (Hossain et al, 2015;Yu et al, 2008). However, we find that Mexican-origin males appear more susceptible to partner influences as related to parenting satisfaction.…”
Section: The Moderating Roles Of Linguistic Acculturation and Parent contrasting
confidence: 99%
“…This finding is in contrast to the broader literature on the impact of partners on parenting outcomes, as most research seems to indicate that women's parenting tends to be more heavily influenced by their partners than does men's (Hossain et al, 2015;Yu et al, 2008). This is an interesting finding, for a few reasons.…”
Section: The Moderating Roles Of Linguistic Acculturation and Parent contrasting
confidence: 74%
“…One study on Hispanic mothers’ and fathers’ caregiving roles showed that mothers spent significantly more time in physical care, doctor visits, and communication with their child or children compared to fathers. 18 Because gender roles in Latino families with respect to caregiving and responsibility for children’s health care decisions tend to fall within the purview of the mother, our intervention primarily focused on mothers, but our literature covers both mothers and fathers. The literature indicates that parents are more likely to report a willingness to vaccinate if they feel their child is susceptible to HPV or cervical cancer, 1922 if they believe the vaccine is effective and provides benefits, 19, 20, 2225 and if they perceive few barriers to accessing the vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that, generally speaking, Latino mothers with stronger ties to the community are more likely to be involved with their children's activities. None of the community-level variables were found to be related to father involvement among Latino immigrants (Hossain et al, 2015). English language use, however, is positively associated with physical care and nurturing activities for Latino fathers (Capps et al, 2010), suggesting that acculturation, using English proficiency as a proxy, increases parental involvement among Latino fathers living in the United States.…”
Section: Parental Involvement Of Immigrants From Latin Americamentioning
confidence: 81%